Socio-psychological factors that influence car preference in undergraduate students: the case of the Czech Republic - Šefara, Denis; Franěk, Marek; Zubr, Václav (Technological and Economic Development of Economy, 2015)
The present study examined the socio-psychological factors (personality dimensions, motives for car use, and materialistic values) that influence car preference in undergraduate students (N = 383). Preferences for particular car types, properties, and brands were studied. The data indicated only a slight correspondence between the personality dimensions of the Big-Five model and car preference. However, individual motives for car use and materialistic values predict preferences for certain car types and even more for car brands. The results demonstrated a clearly defined group of individuals who prefer cars with high performance. These individuals prefer German cars of “prestigious” brands, such as Audi, BMW, and Mercedes-Benz. For these individuals, affective motives, as well as materialistic values are important cues for car use and preference. These findings are discussed in terms of more sustainable modes of travel and campaigns to promote sustainable travel modes. The potential value shift from cars as objects that represent personal freedom and identity to more recent mobile technologies, which might play the same role in the younger generation, is discussed.